A framework for co-developing conservation research projects with stakeholders: a Lake Victoria case study - Van den Broek, Karlijn; Luomba, Joseph; Onyango, Horace O.; Musobya, Moses; Klein, Sina (Lakes & reservoirs, 2020)
Stakeholder engagement has increasingly gained popularity in conservation research since it promotes relevant research that has impact and can inform evidence-based policy. Lake basins can especially benefit from research co-created with stakeholders since these regions tend to face a multitude of conservation challenges while also dealing with many stakeholders that are directly dependent on a lake's resources. Particularly important for successful, co-created research is the first phase of stakeholder engagement, namely the co-development of the research agenda with stakeholders. This phase tends to determine whether or not projects will be funded and implemented, therefore providing a foundation for subsequent realization of a project, as well as the impact of the research findings. The present study provides a framework for the application of stakeholder engagement in co-developing a research agenda, as illustrated through a case study on Lake Victoria in East Africa, concluding with key lessons learned from this case study.